Present concerns : journalistic essays - Lewis, C. S. (Clive Staples), 1898-1963 (C.S. Lewis signature book, 2017)
"A repackaged edition of the revered author's essays in which he deliberates on contemporary issues, from the moral to the spiritual to the practical. C. S. Lewis--the great British writer, scholar, lay theologian, broadcaster, Christian apologist, and bestselling author of Mere Christianity, The Screwtape Letters, The Great Divorce, The Chronicles of Narnia, and many other beloved classics--was one of the foremost religious philosophers of the twentieth century; a thinker whose far-reaching influence on Christianity continues to be felt today. Demonstrating Lewis's wide range of interests, Present Concerns includes nineteen essays that reveal his thoughts about democratic values, threats to educational and spiritual fulfillment, literary censorship, and other timely topics, offering invaluable wisdom for our own times"--